NS19504: A Novel BK Channel Activator with Relaxing Effect on Bladder Smooth Muscle Spontaneous Phasic Contractions - Nausch, Bernhard (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Large-conductance Ca(2+)-activated K(+) channels (BK, K(Ca)1.1, MaxiK) are important regulators of urinary bladder function and may be an attractive therapeutic target in bladder disorders. In this study, we established a high-throughput fluorometric imaging plate reader–based screening assay for BK channel activators and identified a small-molecule positive modulator, NS19504 (5-[(4-bromophenyl)methyl]-1,3-thiazol-2-amine), which activated the BK channel with an EC(50) value of 11.0 ± 1.4 µM. Hit validation was performed using high-throughput electrophysiology (QPatch), and further characterization was achieved in manual whole-cell and inside-out patch-clamp studies in human embryonic kidney 293 cells expressing hBK channels: NS19504 caused distinct activation from a concentration of 0.3 and 10 µM NS19504 left-shifted the voltage activation curve by 60 mV. Furthermore, whole-cell recording showed that NS19504 activated BK channels in native smooth muscle cells from guinea pig urinary bladder. In guinea pig urinary bladder strips, NS19504 (1 µM) reduced spontaneous phasic contractions, an effect that was significantly inhibited by the specific BK channel blocker iberiotoxin. In contrast, NS19504 (1 µM) only modestly inhibited nerve-evoked contractions and had no effect on contractions induced by a high K(+) concentration consistent with a K(+) channel–mediated action. Collectively, these results show that NS19504 is a positive modulator of BK channels and provide support for the role of BK channels in urinary bladder function. The pharmacologic profile of NS19504 indicates that this compound may have the potential to reduce nonvoiding contractions associated with spontaneous bladder overactivity while having a minimal effect on normal voiding.